Magnetic Carbon Nanofibers from Horse Manure via Hydrothermal Carbonization for Methylene Blue Adsorption - Napat Kaewtrakulchai; Ampol Putta; Warit Pasee; Kajornsak Fuangnawakij; Gasidit Panomsuwan; Apiluck Eiad-ua (My University, 2019)
Abstract Disposal and recycle of waste biomass is of great concern. Thermochemically converting the waste biomass to carbon nanomaterials is an interesting because of environmental friendly, low cost and local availability. In this work, magnetic carbon nanofibers have been synthesized by hydrothermal and carbonization of the magnetite preloaded on horse manure which is controllable temperature and additive of catalyst. It was found that Fe is able to form magnetic carbon nanofibers (M-CNFs). Furthermore, magnetic carbon nanofibers were used as an adsorbent for methylene blue adsorption. Synthesized magnetic sorbents exhibited high performance on methylene blue adsorption and it is successfully separated from the water by magnetic separation.
Keywords: Methylene blue; Hydrothermal Carbonization; Carbon fibers; Nanomaterials for catalytic reactions